Inovasi Manajemen Pemasaran dalam Perspektif Islam - Arif, Miftakhul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine how innovative marketing management strategies are implemented in higher education. Strategies to attract new customers and retain old customers require universities to develop a competitive advantage based on the quality of their services. This study uses a qualitative method with a type of library research. The data used in this research comes from scientific articles published in academic journals, research report results, and other related documents. Data was collected using documentation study techniques. Meanwhile, the analysis technique used is content analysis, which aims to evaluate the content of the collected literature. The findings of this research indicate that the marketing management of educational services from the perspective of the Qur'an can be carried out through the methods of bil hikmah, mauidhah hasanah, and al jidal billati hiya ahsan. The orientation and model of service marketing are implemented in a holistic spiritual manner based on religious values.